An Examination of The Factors Affecting Consumer’s Purchase Decision on Prudential Insurance Product - Elsa Ika Marchella Arruan; Ayu Tyas Purnamasari; Muzzamil - - (STIKes Kepanjen, 2022)
The insurance literacy and the insurance ownership especially commercial insurance is relatively low in Indonesia. Meanwhile the insurance is important to mitigate the risks such as accidents, illness, and death. Many factors influencing consumers to buy insurance products. This study aimed to examine the factors affecting consumer’s purchase decision on insurance products particularly Prudential insurance products. This study was observational study using a cross-sectional design with 84 respondents were selected randomly. Data collection is carried out by disseminating questionnaire. Data were analyzed using univariate and bivariate analysis. Furthermore, the results of this study were the majority of the respondents are able to buy insurance products, satisfied with the promotion by the insurance agents, and sure of their decisions to purchase the Prudential insurance products. The promotion by the agents variable have a significant correlation to consumer’s purchase decision on Prudential insurance products.